Why Do We Buy Things that We Don’t Need: Reflections from Neuropsychology - Ramos-Galarza, Carlos (2023)
The process that human mind follows to buy any article involves a series of steps. This work reflects from a neuropsychological point of view, the implication that executive functions have in this process. Inhibitory control, emotional regulation, decision making, planning, cognitive flexibility, error correction, and internal language regulating behavior are the executive functions that are analyzed on the possibility of generating an automatic or conscious behavior to make a purchase, for example, when an article is acquired because there is the need versus when a purchase is made only because of impulsive. As conclusion, evidence of the complex dynamics when buying a thing is left, where it is possible to consider executive functions for future marketing campaigns, thus, increase the sales of a specific product.